The Effectiveness of Rosetta Stone Application for Vocabulary Mastery of Sixth Graders in MI Hidayatul Mubtadiin Jubang-Brebes - Sukron Ma'mun; Irra Wahidiyati (Jurnal Vokasia, 2025)
This study aims to examine the effectiveness of Rosetta Stone application for vocabulary mastery of sixth graders in MI Hidayatul Mubtadiin Jubang-Brebes. This research was motivated by the common issues faced in vocabulary learning, including limited vocabulary, pronunciation difficulties, and monotonous teaching methods. A pre-experimental one-group pre-test and post-test design was used, involving 28 students. They underwent three sessions using Rosetta Stone to learn vocabulary related to verbs, school equipment, and aspirations. The data were analyzed using N-Gain, which resulted in a moderate improvement score (0.3777). The findings demonstrate that integrating technology-based tools like Rosetta Stone can significantly support vocabulary acquisition in primary education. The study highlights the potential of interactive applications in creating engaging learning environments and recommends their broader use in elementary English instruction.